2004
DOI: 10.1007/s00425-004-1328-0
|View full text |Cite
|
Sign up to set email alerts
|

The DNA-binding protease, CND41, and the degradation of ribulose-1,5-bisphosphate carboxylase/oxygenase in senescent leaves of tobacco

Abstract: Plastids bear their own genome, organized into DNA-protein complexes (nucleoids). Recently, we identified a DNA-binding protease (CND41) in the chloroplast nucleoids of cultured tobacco (Nicotiana tabacum L.) cells. In this study, we examine the biochemical function of this novel DNA-binding protease, particularly in senescent leaves, because antisense tobacco with a reduced amount of CND41 showed retarded senescence. Nitrogen-depletion experiments clearly showed that CND41 antisense tobacco maintained green l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(105 citation statements)
references
References 51 publications
7
96
0
2
Order By: Relevance
“…Its sequence is similar to those of aspartic proteases and it exhibits strong proteolytic activity at an acidic pH (Murakami et al 2000). It could be shown that CND41 is involved in Rubisco degradation and in the translocation of nitrogen during senescence (Kato et al 2004). In senescent leaves of barley its expression was shown to be down-regulated (Parrott et al 2007).…”
Section: Cnd41mentioning
confidence: 99%
“…Its sequence is similar to those of aspartic proteases and it exhibits strong proteolytic activity at an acidic pH (Murakami et al 2000). It could be shown that CND41 is involved in Rubisco degradation and in the translocation of nitrogen during senescence (Kato et al 2004). In senescent leaves of barley its expression was shown to be down-regulated (Parrott et al 2007).…”
Section: Cnd41mentioning
confidence: 99%
“…Degradation of some thylakoid proteins such as LHCII seemingly occurs exclusively within chloroplasts and requires the prior release and breakdown of pigments (Hörtensteiner & Feller, 2002;Buchanan-Wollaston et al, 2003a). CND41 protease is believed to be involved in Rubisco degradation and in the translocation of nitrogen during senescence in tobacco leaves (Kato et al, 2004(Kato et al, , 2005. However, the central vacuole and SAVs also play a role here, as they help complete the degradation of Rubisco and other stromal proteins (Martínez et al, 2008).…”
Section: Growth-related Parameters and Photosynthetic Activity Duringmentioning
confidence: 99%
“…In mature chloroplasts, MFP1 is attached to thylakoids; hence, it may possibly anchor the nucleoids to the thylakoid membranes (Jeong et al, 2003). Other well-characterized proteins in nucleoids are a sulfite reductase, which participates in organellar nucleoid organization (Cannon et al, 1999;Chi-Ham et al, 2002;Sekine et al, 2002), and a DNA binding protein CND41 with aspartic protease activity (Murakami et al, 2000), possibly involved in regulation of senescence (Kato et al, 2004).…”
Section: Introductionmentioning
confidence: 99%